Late Cenozoic exhumation in the eastern Junggar Basin: Evidence from zircon (U-Th)/He ages of combustion metamorphic rocks - Bin Chen; Pan Liu; Yan Dong; Changjuan Feng; Zhuang Zhao; Chaoqun Yang; Yixin Dong (PLoS ONE, 2026)
Since the Cenozoic, the peripheral orogenic belts around the Junggar Basin have undergone substantia uplift in response to far-field deformation associated with the India–Asia collision. However, conventional geochronological methods commonly provide only indirect or insufficiently resolved constraints on the timing and geomorphic expression of late Cenozoic uplift and exhumation. Combustion metamorphic (CM) rocks, generated when coal seams are brought into shallow, oxygen-rich conditions during tectonic uplift and denudation and subsequently ignite spontaneously, offer a potential near-surface chronometer for these processes. In this study, we characterized coal maceral composition, rank, and spontaneous combustion tendency; documented the distribution, petrography, and mineral assemblages of CM rocks through field investigations, thin-section observation, and X-ray diffraction; and applied zircon (U-Th)/He dating to constrain the timing of CM rock formation. Three zircon grains define a tightly clustered Middle Pleistocene population with a weighted mean age of 0.63 ± 0.19 Ma, which we interpret as the principal timing of coal seam combustion and CM rock formation. Two older single-grain ages (8.7 ± 0.5 Ma and 87.7 ± 5.4 Ma) are treated cautiously as incompletely reset or inherited pre-combustion thermochronologic components rather than as independent combustion events. The spatial distribution and ages of CM rocks show a clear correspondence with late Cenozoic uplift and exhumation of the orogenic belt. These results demonstrate that zircon (U-Th)/He thermochronology of CM rocks can provide a useful chronological marker for near-surface tectonic processes and offers an additional approach for reconstructing late Cenozoic tectonic evolution in intracontinental orogenic settings.